Montaigne’s discovery of Man The Humanization of a Humanist - Frame, Donald M. 1911-1991 (Columbia University Press, 1955)
Examines the evolution of Montaigne's humanistic views in three stages: beginning with his advocating self-mastery and a firm struggle for consistency against the ills of life to prepare to meet pain and death worthily, then to a period of skeptical crisis in which he critiques human knowledge, and ending with his Epicurean period in which he preached a concentration on simple human goodness rather than on works of stoical supererogation, moderation rather than abstention or excess, and a balance of duties between oneself and others that is neither selfishness nor unselfishness
Description based on online resource; title from PDF title page (publisher's Web site, viewed 30. Apr 2019)
Keywords: Montaigne, Michel Eyquem de -- 1533-1592; PHILOSOPHY / Movements / Humanism